Study on the effect of alginate oligosaccharide combined with Meyerozyma guilliermondii against Penicillium expansum in pears and the possible mechanisms involved. (August 2021) - Han, Junjia; Zhao, Lina; Zhu, Huimin; Dhanasekaran, Solairaj; Zhang, Xiaoyun; Zhang, Hongyin
Abstract: Penicillium expansum is a pathogenic fungus that causes blue mold decay in various fruits and produces toxic substances. This study investigated the effect of alginate oligosaccharide (AOS) combined with Meyerozyma guilliermondii, a biocontrol yeast, to control blue mold decay in pears and the possible physiological biocontrol mechanisms. The results showed that AOS (5 g/L) combined with M. guilliermondii could significantly reduce the blue mold decay incidence and lesion diameter of pears. Moreover, AOS did not affect the growth and reproduction of M. guilliermondii in vitro or in vivo of pears. And could inhibit mycelium development, reduce spore germination rate and inhibit the germ tube elongation of P. expansum . AOS combined with M. guilliermondii increased the activities of superoxide dismutase (SOD), catalase (CAT), polyphenol oxidase (PPO), peroxidase (POD), phenylalanine ammonia-lyase (PAL), chitinase (CHI), total phenol content, and flavonoid content in pears. Overall, our study evidenced that AOS improves the efficacy of M. guilliermondii and could be used to control the blue mold decay in pears. Highlights: M. guilliermondii combined with AOS reduced the blue mold decay of pears. AOS had no effect on the growth and reproduction of M. guilliermondii . AOS combined with M. guilliermondii inhibited the growth of P. expansum in vitro . AOS with M. guilliermondii induced defense-related enzyme activities of pears.